EVALUASI MANAJEMEN LINEN PADA INSTALASI LAUNDRY DI RUMAH SAKIT REGIONAL Dr. SOETOMO SURABAYA - Tiyo Eka N S; Imam Khambali; Sukiran Al Jauhari (GEMA LINGKUNGAN KESEHATAN, 2014)
Dirty Linen was a source of contamination in the hospital laundry division. RSUD Dr. SeotomoSurabaya, the largest referral hospital, where infectious linen sorting using a yellow plastic bag labeled notbeen done by room division. Clean linen also did not stored in the cupboard. This research purposed toevaluate linen management (input factor, process, and output) in RSUD Dr. Soetomo Surabaya.Type of this research was descriptive about evaluative research implementation form. Object of thisresearch was hospital linen management, with the subject of its research are chief of general subdivision,linen personnel of hospital in the room and in laundry unit as well as place and its infrastructure.Types of linen in RSUD Or. Soetomo Surabaya namely : clothing, pants, blanket, coverletllaken,corner, pillowcase, bolster case, tablecloth, towel, duk, gown/skoret, cloth sheet for baby, curtain, andgloves. The linen transport process by room personnel was ineligible. Processes of reception, washing,drying and linen ironing had eligible, but lack of personnel and time limitation there were dirty linens stayin.Storing process, means of facilities and APD usage of personnel was ineligible. The results ofexamination germ numbers gained 1.34 x102 and 1.80x102, that meant was eligible. Based on Dirjen PPMand PLP concerning to Indonesia Hospital Sanitation Manual, clean linen after out from all linenmanagement processes uncontained 6x103 species bacillus spora per square inch.Concluded that exist cloth linen in RSUD Dr. Soetomo Surabaya was good, but clean linen senteveryday unable to meeting the need of room because of lack professional workers. Therefore suggestedin order to staffing of RSUD Dr. Soetomo Surabaya to put several sanitation employee in laundry unit ortraining laundry employee today become a sanitation expert personnel. Instead of suggested immediate tofulfill-lack infrastructure, particularly clean linen storing cabinet.